Marketing Innovation in E-commerce - Bachina, Bhargav (Journal of Global Economy, Business and Finance, 2025)
The internet and e-commerce have emerged as two of the e-commerce and information technology fields' most innovative and rapidly expanding technology, respectively. Internet marketing acts as a computer. mediated marketplace where buyers and sellers can connect, as well as a management and execution platform for business operations like marketing, sales, and distribution. Any action carried out online using internet technology is referred to as internet marketing. It includes not just website advertising but also other online activities like social media marketing, affiliate marketing, email marketing, etc. It might be characterised as marketing strategies used only online. Because so many people use the internet on daily basis for various purposes, internet marketing is a growing. industry